Fracture strength of veneered translucent zirconium dioxide crowns with different porcelain thicknesses. Issue 1 (1st January 2017) - Bakitian, Fahad; Seweryniak, Przemek; Papia, Evaggelia; Larsson, Christel; Vult von Steyern, Per
Abstract: Objective: To evaluate fracture strength of veneered translucent zirconium dioxide crowns designed with different porcelain layer thicknesses. Materials and Methods: Sixty crowns, divided into six groups of 10, were used in this study. Groups were divided according to different thicknesses of porcelain veneer on translucent zirconium dioxide cores of equal thickness (0.5 mm). Porcelain thicknesses were 2.5, 2.0, 1.0, 0.8, 0.5 and 0.3 mm. Crowns were artificially aged before loaded to fracture. Determination of fracture mode was performed using light microscope. Results: Group 1.0 mm showed significantly ( p  ≤ .05) highest fracture loads (mean 1540 N) in comparison with groups 2.5, 2.0 and 0.3 mm (mean 851, 910 and 1202 N). There was no significant difference ( p >.05) in fracture loads among groups 1.0, 0.8 and 0.5 mm (mean 1540, 1313 and 1286 N). There were significantly ( p  ≤ .05) more complete fractures in group 0.3 mm compared to all other groups which presented mainly cohesive fractures. Conclusions: Translucent zirconium dioxide crowns can be veneered with minimal thickness layer of 0.5 mm porcelain without showing significantly reduced fracture strength compared to traditionally veneered (1.0–2.0 mm) crowns. Fracture strength of micro-veneered crowns with a layer of porcelain (0.3 mm) is lower than that of traditionally veneered crowns but still within range of what may be considered clinically sufficient. Porcelain layers of 2.0 mm or thicker should be used where expected loads are low only.